Reflective Models of Service Learning: Connections to Faith, Learning, and Vocation in Pre-Service Teachers - Sipper-Denlinger, Kristen (Christian higher education, 2022)
Previous studies have demonstrated that using guided, targeted, reflections in service-learning (SL) courses can increase student engagement and learning. However, little research has been conducted on how these reflective models can be adapted for faith-based institutions to help students to better integrate faith into their learning experience, also known as faith integration (FI). Employing the Scholarship of Teaching and Learning, this study addressed that gap in the scholarly literature by examining over four semesters various permutations of reflective models used for a service-learning project, how these reflective models can integrate faith reflection, and how using these models has affected students’ perceptions of their spiritual growth, with specific regard to the vocation of those wishing to enter the teaching profession (pre-service teachers). The study concluded that giving students more targeted guidance for reflecting on the connections between faith and service produced more thoughtful and meaningful student response.